Perlindungan Hak Individu Melalui Pendekatan Lex Favor Reo Di Sistem Hukum Pidana - Khibran Nadhir; Hery Firmansyah (UNES Law Review, 2023)
Individual rights are the personal rights of Indonesian citizens in the eyes of the law, including within the criminal law system. The criminal law system in Indonesia recognizes "lex favor reo" as one of the principles in the imposition of criminal punishment. However, Indonesia has undergone a transition from the old Criminal Code (resulting from concordance) to the new Criminal Code as the national Criminal Code. The purpose of this research is to analyze the protection of individual rights with a lex favor reo approach in the criminal law system. The research method used is normative research with a legal approach and the collection of legal materials through library research for descriptive analysis. The results of this research show that Indonesia has protected individual rights in the national Criminal Code as human rights. Furthermore, with the implementation of the new Criminal Code, the principle of lex favor reo, namely the lex favor reo principle, will be resolved based on corrective justice, where criminal sanctions contained in the old Criminal Code are designed to be oriented towards the recovery or compensation for victims of criminal acts. Although there are criminal sanctions, the criminal sanctions in the new Criminal Code also constructively embody the "spirit" of corrective justice.